2013
DOI: 10.1111/evj.12119
|View full text |Cite
|
Sign up to set email alerts
|

Infectious agents associated with diarrhoea in neonatal foals in central Kentucky: A comprehensive molecular study

Abstract: The use of panels rather than individual tests in combination with quantitative toxin gene analysis enables detection of coinfections significantly associated with risk of disease. Several infectious diseases previously not tested for or considered unimportant were found at high prevalence and require further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(114 citation statements)
references
References 33 publications
2
98
3
4
Order By: Relevance
“…Currently, a variety of methods are commercially available for rapid laboratory diagnosis of RVA infection; yet, most of these methods are validated for diagnosis of human RVA, and only a few assays were designed and/or properly validated for veterinary use on samples from different animal species, like calves, foals and piglets (Eing et al, 2001;Greiner et al, 2000;Matthijnssens et al, 2008;Monini et al, 2011;Slovis et al, 2013). The present study was conducted to compare the performance of two commercially available RVA diagnostic kits and one in-house ELISA, for the detection of rotavirus in stool samples from diarrheic foals.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a variety of methods are commercially available for rapid laboratory diagnosis of RVA infection; yet, most of these methods are validated for diagnosis of human RVA, and only a few assays were designed and/or properly validated for veterinary use on samples from different animal species, like calves, foals and piglets (Eing et al, 2001;Greiner et al, 2000;Matthijnssens et al, 2008;Monini et al, 2011;Slovis et al, 2013). The present study was conducted to compare the performance of two commercially available RVA diagnostic kits and one in-house ELISA, for the detection of rotavirus in stool samples from diarrheic foals.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of data revealed that RT-PCR is more accurate than ELISA and RNA-PAGE for the detection of group A rotavirus. Other studies also indicate that PCR is the best confirmatory detection technique for group A rotavirus in faecal samples (Wilde et al, 1990;Husain et al, 1995;Slovis et al, 2014).…”
Section: Detection and Comparative Prevalence Of Group A Rotavirusmentioning
confidence: 99%
“…335,601-565 Lawsonia intracellularis can potentially affect horses of any age, but it is most common in weanling-age foals. 535,539,570,571 Equine coronavirus, also sometimes referred to as equine enteric coronavirus, has been recognized in both foals and adult horses. 566 Escherichia coli is an uncommon cause of diarrhea in foals, unlike in calves and piglets.…”
Section: Conditions Associated With Diarrheamentioning
confidence: 99%
“…Although primarily a respiratory pathogen, Rhodococcus equi also can cause diarrhea, particularly in foals 2 to 4 months of age. [571][572][573][574][575] Since 2011 several outbreaks of equine coronavirus have been identified in adult horses, causing it to be named as an emerging pathogen. However, enterotoxigenic strains, characterized by the presence of virulence factors, have been identified in foals.…”
Section: Conditions Associated With Diarrheamentioning
confidence: 99%